Frontal engagement in perceptual integration under low subjective visibility - Jisub Bae; Koeun Jung; Oliver James; Satoru Suzuki; Yee Joon Kim (NeuroImage)
We investigated how spatiotemporal neural dynamics underlying perceptual integration changed with the degree of conscious access to a set of backward-masked pacman-shaped inducers that generated the percept of an illusory triangle. We kept the stimulus parameters at a fixed near-threshold level throughout the experiment and recorded electroencephalography from participants who reported the orientation and subjective visibility of the illusory triangle on each trial. Our multivariate pattern analysis revealed that posterior and central areas initially used dynamic neural code and later switched to stable neural code. The transition from dynamic to stable neural code in posterior area occurred increasingly later and eventually disappeared with decreasing conscious access. Anterior area primarily used stable neural code which waned with decreasing conscious access, but increased at below-median visibility and remained even when stimulus awareness was minimal. These results demonstrate differential spatiotemporal neural dynamics underlying perceptual integration depending on conscious access and emphasize a unique role of anterior area in processing integrated shape information especially under low subjective visibility.